2016
DOI: 10.1016/j.ccell.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-126 Orchestrates an Oncogenic Program in B Cell Precursor Acute Lymphoblastic Leukemia

Abstract: MicroRNA (miRNA)-126 is a known regulator of hematopoietic stem cell quiescence. We engineered murine hematopoiesis to express miRNA-126 across all differentiation stages. Thirty percent of mice developed monoclonal B cell leukemia, which was prevented or regressed when a tetracycline-repressible miRNA-126 cassette was switched off. Regression was accompanied by upregulation of cell-cycle regulators and B cell differentiation genes, and downregulation of oncogenic signaling pathways. Expression of dominant-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Several reports have described an oncogenic role for miR-126, such as the inhibition of apoptosis in acute lymphoblastic leukemia [64] and the promotion of gastric carcinogenesis [65]. Many studies have highlighted the strong downregulation of miRNA-126 in several cancer types such as pancreatic [66], lung, and kidney ones [67, 68].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described an oncogenic role for miR-126, such as the inhibition of apoptosis in acute lymphoblastic leukemia [64] and the promotion of gastric carcinogenesis [65]. Many studies have highlighted the strong downregulation of miRNA-126 in several cancer types such as pancreatic [66], lung, and kidney ones [67, 68].…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of human neuroendocrine prostate cancer from prostate epithelial cells is driven by N-Myc and activated AKT1, as evidenced by the in vivo transformation in NSG mice of prostate basal epithelial cells overexpressing N-Myc and myrAKT1 [45]. MiRNA-126 stabilizes B-ALL in a proliferative B cell precursor state by targeting cell cycle/apoptosis and p53 response genes and antagonizing miRNA-126 in human B-ALL reduces disease burden in its PDX model [46]. Millions of somatic mutations have been found in cancers through genome sequencing, but the functional impact of most mutations is poorly understood.…”
Section: Pdx Models In Basic Cancer Researchmentioning
confidence: 99%
“…However, overexpression of miR-132 on a Eμ-Myc background in mice, resulted in improved animal survival when compared to Eμ-Myc mice, suggesting that miR-132 may yield a protective effect, at least in this mouse model [26]. Mice overexpressing miR-126 in lin − HSPCs, have developed precursor B cell leukemia [85]. Indeed, RNA-seq analyses of human CD34 + progenitor cells and murine B cell acute lymphoblastic leukemia (B-ALL) cells overexpressing or lacking miR-126, suggested that this miRNA could modulate the expression of genes implicated in the p53 tumor suppressor signaling pathway, where cyclin-dependent kinase inhibitor 2a-interacting protein, Cdkn2aip , was validated as a direct target of miR-126 in a luciferase reporter assay [85].…”
Section: Mirnas In B Cell Lymphomagenesismentioning
confidence: 99%
“…Mice overexpressing miR-126 in lin − HSPCs, have developed precursor B cell leukemia [85]. Indeed, RNA-seq analyses of human CD34 + progenitor cells and murine B cell acute lymphoblastic leukemia (B-ALL) cells overexpressing or lacking miR-126, suggested that this miRNA could modulate the expression of genes implicated in the p53 tumor suppressor signaling pathway, where cyclin-dependent kinase inhibitor 2a-interacting protein, Cdkn2aip , was validated as a direct target of miR-126 in a luciferase reporter assay [85]. The leukemia in miR-126 overexpressing mice can regress if expression of miR-126 is abolished, demonstrating that the malignant cells may be addicted to miRNA-126 expression[85].…”
Section: Mirnas In B Cell Lymphomagenesismentioning
confidence: 99%